2011
DOI: 10.1007/s00595-010-4329-6
|View full text |Cite
|
Sign up to set email alerts
|

Physiological evaluation of residual stomach motility after local resection in conscious dogs

Abstract: Gastric function was maintained after gastric local resection, although its motility decreased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…A previous report indicated that the bioavailability of mosapride in dogs was lower than that in other species, such as monkeys [10]. Considering the present results and previous reports [8,15], the recommended dose of mosapride in dogs is 0.75 to 2 mg/kg. Doses of up to 2 mg/kg may be required in low-response patients or cases of severe gastric motility disorders, such as gastroparesis.…”
supporting
confidence: 50%
See 1 more Smart Citation
“…A previous report indicated that the bioavailability of mosapride in dogs was lower than that in other species, such as monkeys [10]. Considering the present results and previous reports [8,15], the recommended dose of mosapride in dogs is 0.75 to 2 mg/kg. Doses of up to 2 mg/kg may be required in low-response patients or cases of severe gastric motility disorders, such as gastroparesis.…”
supporting
confidence: 50%
“…Mosapride is also registered as a prokinetic agent in dogs (Pronamid; DS Pharma Animal Health Co., Ltd., Osaka, Japan) in Japan and has been used for the control of upper gastrointestinal symptoms, such as anorexia and vomiting, associated with gastrointestinal motility disorders. Previous reports demonstrated that mosapride (1 mg/kg) enhanced gastric antral motility in dogs [8,15], but the appropriate oral dose that produces prokinetic action without any adverse effects has not been determined. The main purpose of the present study was to assess the dose of mosapride as oral drug that had gastric prokinetic action in dogs.…”
mentioning
confidence: 99%
“…We believe that a potential influence on gastric motility after LECS is resection of Latarjet’s branch of the vagal nerve and gastric deformity. Kubota et al performed local gastric resection of either the lesser or the greater curvature in dogs and physiologically evaluated postoperative residual gastric motility [19]. The authors reported that resection of the lesser curvature involves resection of Latarjet’s branch of the vagal nerve, which is distributed in the lesser curvature, and decreased gastric motor activity, which probably resulted in impaired residual gastric motility.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, mosapride citrate has been used as a prokinetic agent for the treatment of dyspeptic symptoms of gastrointestinal disorders such as chronic gastritis, functional dyspepsia, irritable bowel syndrome, and gastric esophageal reflux disease [4]. Mosapride also enhances upper gastrointestinal motility in dogs [7, 12, 13] and has been used for the control of upper gastrointestinal symptom, such as anorexia and vomiting that are associated with gastrointestinal motility disorders. In horses, the oral administration of mosapride can increase the electrical activity of the small intestine and caecum, which suggests that mosapride promotes motility in the small intestine and caecum of horses [11].…”
mentioning
confidence: 99%
“…Ruminal motility was recorded on a polygraph (MP100A, BIOPAC Systems Inc., Santa Barbara, CA, U.S.A.) by connecting the lead wires of the transducers to the connecting cables from the amplifiers (DA100, BIOPAC Systems Inc.), was digitized by an analog-to-digital converter, and continuously recorded on a computer for analysis. To assess the amplitude of ruminal motility quantitatively, the motility index [7, 13] was determined. The motility index given by the processing system corresponded to the measurements of the area surrounded by the contraction wave and base line.…”
mentioning
confidence: 99%